ACADEMIC SELF-EFFICARY, PERSONAL RESPONSIBILITY, AND CLINICAL PRACTICE READINESS AMONG NURSING STUDENTS : A CROSS-SECTIONAL STUDY - Fitriani, Fitriani; Andaz, Amzal Mortin; Agus, Al Ihksan; Nisa, Khairun (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2026)
Introduction: Nursing education aims to produce graduates who are academically competent and professionally prepared for complex clinical practice. Clinical practice readiness is a key indicator of students’ successful transition to the real work environment. While previous studies highlight the influence of academic self-efficacy and personal responsibility, no research in Indonesia has yet examined their correlation with clinical practice readiness.Objective: This study aimed to describe and analyze the correlation between academic self-efficacy and personal responsibility with clinical practice readiness in nursing students. Method: This study used a cross-sectional quantitative research method. The population in this study consisted of nursing students at two nursing education institutions in Indonesia with a sample size of 346 respondents selected using the proportionate stratified random sampling technique. The Sociodemographic Questionnaire, The Academic Self-Efficacy Scale, Personal Responsibility Scale, and Readiness for Practice Survey were used in this study. The data were analyzed using multiple linear regression test.Results: The results showed that the overall regression model was significant with a value of F= 50.31 and p-value= <0.001. This shows that simultaneously, gender, semester, GPA, academic self-efficacy, and personal responsibility make a significant contribution to the clinical practice readiness of nursing students. The Adjusted R² value was 0.417 which indicated that about 41.7% variability in the clinical practice readiness of nursing students can be explained by the model. Partially, semester (β = 0.141; p-value= 0.001), academic self-efficacy (β = 0.540; p-value= <0.001), and personal responsibility (β = 0.167; p-value= <0.001) had a significant positive effect on the clinical practice readiness of nursing students where academic self-efficacy was the most dominant predictor that affected the clinical practice readiness of nursing students.Conclusion and Recommendation: Simultaneously, gender, semester, GPA, academic self-efficacy, and personal responsibility made a significant contribution to the clinical practice readiness of nursing students. Tailored support from educational institutions considering demographic and academic characteristics and psychological factors is recommended to optimize nursing students’ clinical readiness.